On the subject matter of International Relations. Issue 5 (17th July 2017) - Albert, Mathias; Buzan, Barry
Abstract: This article deals with the subject matter of International Relations as an academic discipline. It addresses the issue of whether and how one or many realms could legitimately be claimed as the discipline's prime subject. It first raises a number of problems associated with both identifying the subject matter of IR and 'labelling' the discipline in relation to competing terms and disciplines, followed by a discussion on whether, and to what degree, IR takes its identity from a confluence of disciplinary traditions or from a distinct methodology. It then outlines two possibilities that would lead to identifying IR as a discipline defined by a specific realm in distinction to other disciplines: (1) the 'international' as a specific realm of the social world, functionally differentiated from other realms; (2) IR as being about everything in the social world above a particular scale . The final section discusses the implications of these views for the study of International Relations.